2021
DOI: 10.1177/10538151211032211
|View full text |Cite
|
Sign up to set email alerts
|

A Parent-Implemented Shared Reading Intervention via Telepractice

Abstract: We describe a study of the internet-based Parent-Implemented Communication Strategies–Storybook (i-PiCSS), an intervention designed to train and coach parents to use evidenced-based naturalistic communication teaching (NCT) strategies (i.e., modeling, mand-model, and time delay) and RTs while reading storybooks with their young children with disabilities. Three participating parents were trained and coached via telepractice technologies (videoconferences, video editing software). Zoom software was used for vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…While this study occurred in both a face-to-face and an online format, future research could determine whether one format is better than the other using a single-case comparison design (e.g., parallel treatments). Finally, future research could focus on coaching other teachers or parents to use shared reading with students with ESN, as in a study by Akemoglu et al (2021) that used naturalistic communication teaching strategies (e.g., modeling, mand-model, time delay) to train parents to increase language and communication during shared reading with children.…”
Section: Discussionmentioning
confidence: 99%
“…While this study occurred in both a face-to-face and an online format, future research could determine whether one format is better than the other using a single-case comparison design (e.g., parallel treatments). Finally, future research could focus on coaching other teachers or parents to use shared reading with students with ESN, as in a study by Akemoglu et al (2021) that used naturalistic communication teaching strategies (e.g., modeling, mand-model, time delay) to train parents to increase language and communication during shared reading with children.…”
Section: Discussionmentioning
confidence: 99%
“…At lower primary, children are expected to have already developed reading readiness skills (Mugalavai, 2012) However, knowledge and information about the mechanisms of parental involvement with lower primary school pupils' reading skills and factors influencing parental involvement in Kenya remain inadequate. If parents do not guide their children for example in reading, to prepare them to be successful in school and reading, they can only do so at their own and their children's peril (Akemoglu, 2022;Dupont et al, 2022). Kenya recently adopted a new Competence Based Curriculum (CBC) which is initially being implemented from preschool to grade three.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a growing body of literature supporting the effectiveness of in-person social skills interventions (Gates et al, 2017 ; Hume et al, 2021 ), research on telehealth administration of social skills interventions is more limited. For example, only a few studies have found that parental instruction provided via telehealth results in increased social communication skills (Akemoglu et al, 2021 ; Baharav & Reiser, 2010 ; Hao et al, 2021 ; Meadan et al, 2016 ). Additionally, Cihon and colleagues’ ( 2021 ) investigation of a telehealth administration of the Cool Versus Not Cool intervention found that the three children in the study achieved mastery of the program’s seven steps, though only two exhibited generalization of these skills.…”
Section: Introductionmentioning
confidence: 99%